Analysis of Spectral Characteristics of Certain Polyene Antibiotics in the Presence of Dmso and Cholesterol - G. H. Sultanova; T. J. Pashazade; Kh. M. Kasumov (Антибиотики и Химиотерапия)
This work presents ultraviolet (UV) spectra of various concentrations of polyene antibiotics. The spectra of Levorin and Amphotericin B diﬀer in three main absorption maxima. The maximum absorption spectra of antibiotics vary in the range of 370–430 nm. UV absorption spectra reﬂect the characteristic spectrum of polyenes belonging to this class. Amphotericin B and Levorin in combination with cholesterol lower the maximum of the UV absorption spectra. Analysis of the obtained results shows that cholesterol molecules, combining with double-bond systems of Amphotericin B and Levorin, gradually reduce the maximum absorption of UV spectra, which creates opportunities for their more active use in various ﬁelds of biomedicine.